THE ESSENCE OF THE CONCEPT OF “LIFE STRATEGY” IN THE CONTEXT OF TRANSFORMATION OF SOCIO-CULTURAL SPACE - Amelina, Victoria (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article outlines the main problems of determining the essence of the characteristics of the concept of “life strategies” and the need for a parallel analysis of the essentially similar concepts of “life strategies” and “behavioral strategies”. The history of the formation of the concept of “life strategy” in the scientific discourse of sociological, sociopsychological, sociophilosophical and pedagogical concepts is highlighted, which allows us to generalize the main features in relation to the main terms. It was found that the most important characteristics of life strategies are value system, level of responsibility, degree of self-awareness. The conducted research has confirmed that the key aspects of determining the correct life strategy are the individual’s decision to shape his or her future in accordance with the defined goal, which is important for person’s own values and needs. As a result, the goals of life strategies, which are related to people’s understanding of the meaning of their own life, were analysed in the conducted research. It was established that “love”, “continuation of oneself in future generations” and “calm, safe life” took the first three places in all age groups. The actual people’s life attitudes, which depend on the choice of ways to realize the goals of life strategies, are determined. The majority of respondents believe that they can achieve success in life by relying on themselves, but at the same time, complying with the laws. Moreover, the majority of respondents assess their own position in life as active. It has been established that over the years, people’s expectations of the government’s participation in protecting their interests (the state, deputies, and the president personally) have grown significantly. Considering the phenomenon of the formation of “life strategies” in the context of the transformation of the socio-cultural space from different perspectives, it is possible to conclude that the key aspects are unchanged. However, the role of spiritual maturity, experience, purpose, abilities, and potential in the formation of a correct life strategy in the present time, which is the scientific novelty of the work, has not been sufficiently investigated.